A Translation Shift Analysis Of Verbs And Verb PhrasesIn Life Of Pi Into Krhidupan Pi Subtitling - Janatiyah, Janatiyah, Dra. Dwi Haryanti, M. Hum, Siti Fatimah, S.Pd. M.Hum (2013)
The goals of this research paper are to classify the translation shifts of verbs and verb phrases and to explain the equivalence of verbs and verb phrases in Life of Pi into Kehidupan Pi subtitling. This research is descriptive qualitative research. The objects are the verbs and verb phrases found in Life of Pi into Kehidupan Pi Subtitling. The data are the verbs and verb phrases that undergo translation shift in Life of Pi into Kehidupan Pi subtitling. The documentation method is used to collect the data from both of the subtitling. The result of the study shows that first, there are 453 data of verbs and verb phrase that are not included in translation shift (66.81%), and finds 225 data of verbs and verb phrases that are included in translation shift (33.19%). From the 225 data translation shift of verbs and verb phrases, they are: 1) 8 data or 1.2% of verb into noun, 2) 2 data or 0.3% of verb into adverb, 3) 5 data or 0.7% of active verb into passive verb and vice versa, 4) 16 data or 2.4% of untranslated verb, 5) 1 datum or 0.1% of linking verb into adverb, 6) 22 data or 3.2% of verb into noun phrase, 7) 23 data or 3.4% of verb into verb phrase, 8) 31 data or 4.6% of verb phrase into noun phrase, 9) 4 data or 0.6% of active verb phrase into passive verb phrase and vice versa, 10) 91 data or 13.4% of verb phrase into verb, 11) 1 datum or 0.1% verb phrase into noun, 12) 2 data or 0.3% of verb phrase into adjective, 13) 2 data or 0.3% of verb phrase into adverb, and 14) 17 data or 2.5% of verb phrase (grammatical) into lexical. Second, there are 224 data or 99.56% from 225 data that belongs to equivalent translation, and there is only one datum or 0.44% that belongs to non-equivalent translation. So, the writer concludes that the equivalence of verbs and verb phrases in Life of Pi into Kehidupan Pi subtitling is equivalent translation.